Work reality perceived by individuals with impairments: A biopsychosocial experience. - Coelho, Cecília Martins; Sampaio, Rosana Ferreira; Luz, Madel Therezinha; Mancini, Marisa Cotta (Work, 2013)
BACKGROUND: Individuals with different impairments are working in the formal and/or informal market despite physical and attitudinal barriers. To date, few studies have addressed this situation from the perspective of the individuals. OBJECTIVE: Apprehend factors that restrict work performance in the perspective of workers with impairments and identify the strategies employed and the difficulties faced. PARTICIPANTS: Individuals with impairment who exercised paid activities. METHODS: Thirty semi-structured interviews and eleven observations of individuals in work activities. RESULTS: Limitations stemming from participants' disability and health status had an influence over their execution of tasks, but did not compromise work performance. Environmental factors that impacted as facilitators or barriers were: lack of preparation of colleagues, employers, education and rehabilitation systems; attitudes and coexistence; accessibility, implementation of land use policies, urban structures and transportation; products and technology; and distributive policies. Personal factors (upbringing, self-esteem, good mood, outgoingness, communicability, willpower, age and how the disability was acquired) also influenced participation at work. Important strategies included recognizing and sharing capabilities and needs, which minimized or eliminated difficulties at work. CONCLUSIONS: Workers with impairments developed effective strategies for dealing with adverse situations, which remained in the individual realm. Working with impairments is a complex experience that demands overcoming old paradigms.